Gastrografin as an alternative booster to sodium phosphate in colon capsule endoscopy: safety and efficacy pilot study - Togashi, Kazutomo; Fujita, Tomoki; Utano, Kenichi; Waga, Eriko; Katsuki, Shinichi; Isohata, Noriyuki; Endo, Shungo; Lefor, Alan K. (Endoscopy International Open, 2015)
Background and study aims: Sodium phosphate is a key component of bowel preparation regimen for colon capsule endoscopy (CCE), but may cause serious complications. The aim of this study is to evaluate the use of Gastrografin, substituted for sodium phosphate, in CCE bowel preparation.Patients and methods: In total, 29 patients (median age 64 years; 23 females) underwent CCE, covered by the national health insurance system of Japan. All had a history of laparotomy and/or previously incomplete colonoscopy. On the day before examination, patients ingested 1 L of polyethylene glycol + ascorbic acid with 0.5 L of water in the evening, and again the same laxative on the morning of examination. After capsule ingestion, 50 mL of Gastrografin diluted with 0.9 L of magnesium citrate was administered, and then repeated after 1 hour.Results: The capsule excretion rate was 97 % (28/29). The median colon transit time was 2 hours 45 minutes and rapid transit (< 40 minutes) through the colon occurred in one patient (3.4 %). Bowel cleansing level was adequate in 90 % of patients. The polyp (≥ 6 mm) detection rate was 52 %. Diluted Gastrografin was well tolerated by patients. No adverse events occurred.Conclusion: Gastrografin can be an alternative to sodium phosphate in CCE bowel preparation regimen.